PEMBIARAN TERHADAP SUATU TINDAK PIDANA OLEH PENYIDIK KEPOLISIAN - Nainuri Suhadi (Law Department, University of Widya Gama Mahakam Samarinda, 2024)
Many criminal justice seekers feel that they do not get a sense of justice when reporting crimes to police investigators, and the phenomenon of investigators not wanting to bother or take the initiative in carrying out investigative actions (omission) for various reasons, and increasingly becoming clearer, will give rise to legal certainty. Data collection in this writing uses the nomative research method by collecting materials, both primary and secondary data That from the authorities granted by law to Police Investigators and Inspectors, investigators and investigators have legal standing and legitimacy to realize and create a sense of security for the community, which is the obligation of Police Investigators and Investigators. So if someone has been given the authority to carry out an investigation but does not carry out the investigation, it is committing a violation of the law, in the category of an unlawful act